Presence of vertebrate coprolites from the Alagoas Basin, Lower Cretaceous - Souto, Paulo Roberto de Figueiredo; Schwanke, Cibele (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
Coprolites collected from sedimentary rocks of the Maceió Formation, Alagoas Basin are analyzed for the first time. The specimens consist of two complete coprolites of cylindrical morphology that are preserved in commonly fluidized medium- to coarse-grained sandstone interbedded with medium- to fine-grained sandstone and dark shale deposited during the Meso Aptian-Lower Albian. The paleovertebrate community recorded in the Maceio Formation consists of the open sea fish species Vinctifer and Cladocyclus, and the freshwater fish species Ellimma and Dastilbe. The morphostructural aspects of the specimens and the type of sedimentary rocks where they were found suggest that the coprolites were produced by adult carnivore vertebrate, which is evidenced by the chemical composition and thickness of the studied specimens. This study records predatory behavior in this litoraneous community during phases of marine transgression.